Differences in clinical results after LINAC-based single-dose radiosurgery versus fractionated stereotactic radiotherapy for patients with vestibular schwannomas - Combs, Stephanie; Welzel, Thomas; Schulz-Ertner, Daniela; Huber, Peter E.; Debus, Jürgen (International journal of radiation oncology, biology, physics, 2010)
PURPOSE: To evaluate the outcomes of patients with vestibular schwannoma (VS) treated with fractionated stereotactic radiotherapy (FSRT) vs. those treated with stereotactic radiosurgery (SRS). - METHODS AND MATERIALS: This study is based on an analysis of 200 patients with 202 VSs treated with FSRT (n = 172) or SRS (n = 30). Patients with tumor progression and/or progression of clinical symptoms were selected for treatment. In 165 out of 202 VSs (82%), RT was performed as the primary treatment for VS, and for 37 VSs (18%), RT was conducted for tumor progression after neurosurgical intervention. For patients receiving FSRT, a median total dose of 57.6 Gy was prescribed, with a median fractionation of 5 x 1.8 Gy per week. For patients who underwent SRS, a median single dose of 13 Gy was prescribed to the 80% isodose. - RESULTS: FSRT and SRS were well tolerated. Median follow-up time was 75 months. Local control was not statistically different for both groups. The probability of maintaining the pretreatment hearing level after SRS with doses of < or =13 Gy was comparable to that of FSRT. The radiation dose for the SRS group (< or =13 Gy vs. >13 Gy) significantly influenced hearing preservation rates (p = 0.03). In the group of patients treated with SRS doses of < or =13 Gy, cranial nerve toxicity was comparable to that of the FSRT group. - CONCLUSIONS: FSRT and SRS are both safe and effective alternatives for the treatment of VS. Local control rates are comparable in both groups. SRS with doses of < or =13 Gy is a safe alternative to FSRT. While FSRT can be applied safely for the treatment of VSs of all sizes, SRS should be reserved for smaller lesions.